Genetic parameters and correlations in growth and wood density traits of Balfourodendron riedelianum based on provenance and progeny testing - Longui, Eduardo L.; de Lima, Israel L.; Paneque, Letícia; Machado, José A.R.; Freitas, Miguel L.M. [UNESP]; Sebbenn, Alexandre M. [UNESP] (De Gruyter, 2024)
Balfourodendron riedelianum is an important timber species of South America used in civil construction and carpentry. Knowing the genetic variation, heritability and correlation between traits is an essential prerequisite for guiding selection of the best genotypes in tree improvement. In this study, growth (diameter and height) and wood density (mean, pith, middle and bark position) traits were investigated in 30-year-old trees planted in a B. riedelianum provenance and progeny test established in two sites, Luiz Antônio (LA) and Pederneiras (PE), in São Paulo State (Brazil). ANOVA results showed significant differences between sites for all traits, among provenances and families for wood density traits in the LA site and among families for growth traits in PE. Provenance x site and family x site interactions were significant for almost traits, and genetic correlation between sites was low for all traits (0.17-0.20). Genetic variation (CVg ) was higher (4.0-5.4 %) and mean family heritability (ℎm2 ) was lower for growth (0.12-0.20) compared to wood density (CVg: 2.3-3.8 %, ℎm2 : 0.31-0.59) traits. Genetic correlation was significantly positive and ranged from moderate to high between growth traits (0.47-0.68) and between wood density traits (0.42-0.83) and non-significant between growth and wood density (-0.22-0.30) traits. An analysis of different radial positions showed that heritability tended to increase from pith to the bark position. Our results show a lower environmental effect on wood density traits, allowing the possibility of selecting superior provenances and families with high wood quality in breeding programs in both sites.
Keywords: commercial wood; genotype by environment interaction; heritability; tree species; wood properties